The Role of Hyperbole and Metaphor in Film: Strengheting Emotional Impact, Humor, and Viewer Engagement - Manu, Hendrik Ori; Mikhael Misa; Hesni Neno (International Journal of Language and Literature, 2024)
Figurative language plays a crucial role in storytelling by enriching the narrative, deepening character development, and clarifying the expression of themes. Although its use has been widely studied in various forms of media, research on the application of figurative language in animated films is still limited. Therefore, this study aims to identify and categorize the types of figurative language in Migration and analyze its contribution to the storytelling of the film. This study uses a descriptive qualitative approach with the method of data collection through in-depth analysis of dialog and film scenes. Figurative expressions were categorized based on Leech's typology, and the analysis focused on the frequency and function of various language styles in building the narrative. The results show that hyperbole and metaphor are the most dominant language styles, appearing eight times each, followed by irony seven times. Personification was found twice, while simile only appeared once. Litotes and metonymy were not found, indicating selectivity in the use of figurative language in this movie. Overall, hyperbole and metaphor contribute significantly to enhancing emotional depth, humor, and audience engagement. The implications of this research are useful for filmmakers and educators, highlighting the importance of figurative language in cinematic narratives. Further research could explore audience response, cross-genre comparisons, as well as the potential of animated films in language education.